2019
DOI: 10.3389/fmicb.2019.00621
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Microbial Dynamics in Response to an Induced Wetting Event in Antarctic Dry Valley Soils

Abstract: The cold deserts of the McMurdo Dry Valleys (MDV), Antarctica, host a high level of microbial diversity. Microbial composition and biomass in arid vs. ephemerally wetted regions are distinctly different, with wetted communities representing hot spots of microbial activity that are important zones for biogeochemical cycling. While climatic change is likely to cause wetting in areas not historically subject to wetting events, the responses of microorganisms inhabiting arid soils to water addition is unknown. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 73 publications
(126 reference statements)
3
33
4
Order By: Relevance
“…The similar observation was found in other extreme environments, e.g., Antarctic supraglacial habitats, high Alpine mountains, and Arctic soils (Boetius et al, 2015; Malard and Pearce, 2018). Inconsistently, in the McMurdo Dry Valleys, Acidobacteria, and Actinobacteria dominated soil bacterial communities, which may be related to soil characteristics (Pointing et al, 2009; Niederberger et al, 2019). Gammaproteobacteria constituted a major fraction of Proteobacteria in this study, which also were often found in Arctic and Antarctic sea ice (Boetius et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The similar observation was found in other extreme environments, e.g., Antarctic supraglacial habitats, high Alpine mountains, and Arctic soils (Boetius et al, 2015; Malard and Pearce, 2018). Inconsistently, in the McMurdo Dry Valleys, Acidobacteria, and Actinobacteria dominated soil bacterial communities, which may be related to soil characteristics (Pointing et al, 2009; Niederberger et al, 2019). Gammaproteobacteria constituted a major fraction of Proteobacteria in this study, which also were often found in Arctic and Antarctic sea ice (Boetius et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The first expeditions and studies in Antarctica suggested that this territory as sterile and with limited microbial activity (Cameron et al, 1968). However, in the recent years a large number of studies have demonstrated a high diversity of microorganisms with structured trophic chains that form functional microbial communities (Cary et al, 2010;Teixeira et al, 2013;Niederberger et al, 2015Niederberger et al, , 2019Jorquera et al, 2016;Pudasaini et al, 2017;Durán et al, 2019). Over the years, a number of particular characteristics of Antarctic environment have been discussed and investigated.…”
Section: Extreme Microbiome To the Service Of Sustainable Agriculturementioning
confidence: 99%
“…However, there are still important questions which remain unanswered. Studies of Antarctic soil microbial composition, outside of manipulation experiments such as the addition of water [ 128 ], have been performed at single time points. Such experiments do not permit valid conclusions on how the microbial communities change over time.…”
Section: Gaps In Current Knowledgementioning
confidence: 99%